Analysis of Digital Media Usage in Promoting Communication Skills in Early Childhood - Sovia Ikhwani Putri Sovia; Silvio Waisbord Silvio (Feedback International Journal of Communication, 2024)
Digital media has become an omnipresent element in the lives of young children. This study aims to analyze the usage of digital media in promoting communication skills in early childhood. The proliferation of smartphones, tablets, and other digital devices has revolutionized how children interact with information and communicate with others. However, concerns have been raised regarding the potential impact of excessive screen time on children's development, particularly in areas such as language acquisition and social skills. This research employs a mixed-method approach, combining quantitative surveys and qualitative interviews with parents and educators of children aged 2 to 6 years. Quantitative data will be gathered to examine the frequency and duration of digital media usage among young children, while qualitative insights will delve into the perceived benefits and drawbacks of digital media on communication skills development. Additionally, observations of children's interactions with digital media tools will provide contextual understanding. The findings of this study are expected to contribute to a nuanced understanding of the role of digital media in early childhood communication development. By identifying effective usage patterns and potential pitfalls, educators and parents can make informed decisions regarding the integration of digital media into early childhood education and upbringing. Ultimately, this research aims to inform strategies that leverage digital media to enhance rather than hinder communication skills in young children, ensuring their holistic development in today's digital age.